The impact of structural reforms on productivity. The role of the distance to the technological frontier - Fontoura Gouveia, Ana; Santos, Silvia; Gonçalves, Inês (Paris, 2017)
"In recent years, literature has linked structural reforms with productivity growth. Considering Portugal’s recent comprehensive reform agenda, this topic acquires particular relevance. Using data for Portuguese firms for the period 2006-2014, this paper assesses the impact of structural reforms on firms’ productivity. In line with existing literature, the analysis shows that most reforms entail long-term gains, despite, in some reform areas, the existence of short-term costs. In general, there are important differences across reform areas and across firms, namely when comparing firms with different productivity levels. The firms’ distance to the technological frontier mediates the impact of reforms, either by potentiating its effects or by curbing them, depending on the reform area."